Taking a common concern approach to economic inequality : implications for (cooperative) sovereignty over corporate taxation - Beyleveld, Alexander D. (World Trade Institute advanced studies, 2022)
"Are countries capable of reducing economic inequality under conditions of contemporary globalisation without cooperating and coordinating with other countries? While states are far from powerless to effect distributional change within their own sovereign space, Taking a Common Concern Approach to Economic Inequality makes the case that cooperation and coordination is indeed necessary, especially in relation to corporate taxation. It accordingly contemplates the utility of a transnational taxation system that is embedded in cooperative sovereignty through the recognition of rising economic inequality and its deleterious effects, including how increasingly unequal distributions within countries make transnational cooperation and coordination efforts less likely, as a common concern of humankind"--